Timing of International Bailouts - Kim, Se-Jik (IMF Working Papers; Working Paper, 2004)
This paper proposes that international rescue financing should not be provided to a country where a crisis first occurs, but rather to any country that suffers a subsequent crisis. Such a timing-based lending facility can be Pareto-superior to both laissez-faire and existing international crisis lending facilities, when domestic governments have more information on their own economies than does the international lender of last resort. The new facility mitigates moral hazard owing to information asymmetry by not rescuing the first-hit country. At the same time, it limits crisis contagion by rescuing countries in subsequent crises. Even in the presence of common shocks, the timing-based facility can reduce global risks of crisis because it induces countries to undertake greater crisis-prevention efforts so as not to become the first country hit.